Four-electrode probe for plasma studies in the GOL-NB multiple-mirror trap. (11th November 2021) - Sidorov, E.N.; Batkin, V.I.; Burdakov, A.V.; Ivanov, I.A.; Kuklin, K.N.; Mekler, K.I.; Nikishin, A.V.; Postupaev, V.V.; Rovenskikh, A.F.
Abstract: A system of four-electrode Langmuir probes developed for the GOL-NB multiple-mirror trap is discussed. The system is used for studies of a low-temperature start plasma (10 19 –10 20 m -3, 5 eV) that fills the device during the initial phase of the experiment. The probe allows simultaneous measurements of plasma density, electron temperature and radial electric field. The accuracy of the probe measurements is also discussed.